2005
DOI: 10.1152/ajpheart.00004.2005
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic cardiovascular regulation in subjects with acute mountain sickness

Abstract: The aims of this study were 1) to evaluate whether subjects suffering from acute mountain sickness (AMS) during exposure to high altitude have signs of autonomic dysfunction and 2) to verify whether autonomic variables at low altitude may identify subjects who are prone to develop AMS. Forty-one mountaineers were studied at 4,559-m altitude. AMS was diagnosed using the Lake Louise score, and autonomic cardiovascular function was explored using spectral analysis of R-R interval and blood pressure (BP) variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
45
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 35 publications
(47 reference statements)
7
45
1
Order By: Relevance
“…In NH and in HH, AMS mean scores are related to ventilatory variables (Df in NH, V T in HH) and to CpO 2 whereas in NH, AMS mean scores are also Eur J Appl Physiol (2007) 100:193-205 203 related to HCR (P = 0.04). An exaggerated chemoreflex activity could explain the relationships between these cardioventilatory variables and AMS means scores, as suggested by Lanfranchi et al (2005). Consequently, CpO 2 appears still to be an important variable to predict AMS mean scores in our experimental conditions.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In NH and in HH, AMS mean scores are related to ventilatory variables (Df in NH, V T in HH) and to CpO 2 whereas in NH, AMS mean scores are also Eur J Appl Physiol (2007) 100:193-205 203 related to HCR (P = 0.04). An exaggerated chemoreflex activity could explain the relationships between these cardioventilatory variables and AMS means scores, as suggested by Lanfranchi et al (2005). Consequently, CpO 2 appears still to be an important variable to predict AMS mean scores in our experimental conditions.…”
Section: Discussionmentioning
confidence: 51%
“…More original is the characterization of AMS from a quantitative and not from a qualitative point of view. Indeed, today subjects are divided in AMS+ or AMS-subjects (Richalet et al 1988;Rathat et al 1992;Lanfranchi et al, 2005). This procedure is very interesting but, for medical considerations, it is also interesting for a subject found susceptible to AMS to know the potential AMS severity and the risk of mal-adaptation that he could have during an ascent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier research has shown contradictory findings when evaluating measures of heart rate variability in participants with AMS under hypoxic conditions. For instance, individuals with AMS had elevated LF/HF ratios when subjected to 8-12 h of simulated hypobaric hypoxia (4850 m) [6], whereas in a field study, Lanfranchi et al [7] showed that the LF/HF ratio tended to be lower in 17 participants with AMS than those without. Clearly, further research is warranted to determine the effects of AMS on measures of heart rate variability and the prognostic value of changes in these measures in establishing the risk for AMS.…”
Section: Introductionmentioning
confidence: 96%
“…The leading theory is that HACE is a vasogenic edema (Basnyat and Murdoch, 2003;Hackett and Roach, 2004;Van Osta et al, 2005), due to raised intracranial pressure concomitant to increased permeability of the blood-brain barrier. Experimental studies have demonstrated that stimulation of central noradrenergic output increases such permeability (Raichle et al, 1978); raised sympathetic activity has been documented in humans at high altitude (Reeves, 1993), in particular in individuals suffering from AMS (Lanfranchi et al, 2005). Moreover blood-brain barrier permeability may be increased by several chemical mediators, including iNOS-generated nitric oxide.…”
Section: Discussionmentioning
confidence: 99%